2012
DOI: 10.5433/1679-0359.2012v33n4p1435
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de sementes de pinhão manso em diferentes temperaturas, luz e substratos

Abstract: ResumoA cultura do pinhão manso (Jatropha curcas L.) vem ganhando destaque nos últimos anos pelo seu uso como matéria prima para a produção de biodiesel. Sua reprodução pode ser realizada por estacas e/ou sementes. Neste contexto, se desenvolveu o presente estudo com o objetivo de avaliar o efeito do substrato, temperatura e luz sob a germinação e índice de velocidade de germinação (IVG) de sementes de pinhão manso. O delineamento experimental utilizado foi o fatorial do tipo 4x2x2 sendo quatro temperaturas (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
8
0
2
Order By: Relevance
“…There was no germination below 20 °C, or at 45 °C or above (Dias et al, 2007), while for Martins et al (2008) (Vanzolini et al, 2010). More recently, Pascuali et al (2012), when evaluating different temperatures and substrates for germination, found higher germination at 30 °C in sand substrate and in the absence of light. However, Nobre et al (2007) found higher germination at 30 °C or at 20-30 ºC under light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no germination below 20 °C, or at 45 °C or above (Dias et al, 2007), while for Martins et al (2008) (Vanzolini et al, 2010). More recently, Pascuali et al (2012), when evaluating different temperatures and substrates for germination, found higher germination at 30 °C in sand substrate and in the absence of light. However, Nobre et al (2007) found higher germination at 30 °C or at 20-30 ºC under light.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is no information in the Rules for Seed Testing (Brasil, 2009) on conducting germination tests with seeds of physic nut. In this context, standardized methods should be established for seed quality assessment to enable quality control of marketed lots (Silva et al, 2008;Pinto et al, 2009;Pascuali et al, 2012). The germination test is one of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Souza, Bruno, and Andrade, (2005) verified that seeds of Tabebuia serratifolia stored in laboratory environment (27±3 °C and 62±2% UR) showed total loss of vigor at 120 days of storage. Pascuali, Da Silva, Porto, Silva Filho, and Meneghello (2012), examining the substrate effect, temperature and light under germination and germination speed index (GSI) of jatropha seeds, observed that the highest percentages of germination were obtained at temperatures of 25, 30 and 35 °C, with light and 30 °C in the absence of light for the substrate sand and that sowing between sand without light at 30 °C was the one that best promoted the development of the seedlings, with higher Germinate Speed Index (GSI). The combination of the substrate between sand, temperature of 30 °C and absence of light is the best condition for evaluating the germination and Germinate Speed Index (GSI) of jatropha seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Tests carried out with seeds from other forest species recorded that the thermal range suitable for seed germination of these species are between 20 and 30°C (Pascuali et al, 2012). However, variations can occur even among populations of the same species due to environmental conditions and adaptive and ecological characteristics (Mattana et al, 2012); for example, for other species of the family, Bignoniaceae at 35°C is the most recommended for germination of T. aurea (Pacheco et al, 2008) and Pyrostegia venusta (Ker Gawl.)…”
Section: Resultsmentioning
confidence: 99%